2012
DOI: 10.1590/s2236-89062012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Epifitismo vascular em sítios de borda e interior em Floresta Estacional Semidecidual no Sudeste do Brasil

Abstract: -(Vascular epiphytes at the edge and interior of a Semideciduous Forest in Southeastern Brazil). Epiphytes have a key role as environmental indicators and may reflect the degree of local preservation. This research was performed at the Ipanema National Forest, São Paulo State, Brazil, and aimed to characterize the vascular epiphytic community, taking into consideration its abundance and distribution at forest-interior and edge site. In the survey, 16 species belonging to 12 genera in six families were found. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
1
0
2
Order By: Relevance
“…Their restricted distributions and high environmental specificities and endemism make orchids particularly vulnerable to habitat loss (Adhikari et al 2012;Martinelli & Moraes 2013). Nevertheless, studies on ephiphyte community dynamics have not shown an ecological pattern influenced by edge effects, probably due to the low-density of orchid populations (Bernardi & Budke 2010;Bataghin et al 2012;Bianchi & Kersten 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Their restricted distributions and high environmental specificities and endemism make orchids particularly vulnerable to habitat loss (Adhikari et al 2012;Martinelli & Moraes 2013). Nevertheless, studies on ephiphyte community dynamics have not shown an ecological pattern influenced by edge effects, probably due to the low-density of orchid populations (Bernardi & Budke 2010;Bataghin et al 2012;Bianchi & Kersten 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Bataghin et al (2012), a ocorrência de briófitas epífitas no sistema tem forte relação com as características das árvores que elas usam para suporte -os forófitoscomo arquitetura da copa e inclinação do tronco e galhos, que interferem na umidade do substrato e estabelecimento de diásporos (Barkman, 1958;Cornelissen & ter Steege, 1989). A ocorrência também está relacionada à rugosidade e acidez do córtex (Acebey et al, 2003), assim como ao diâmetro e idade do forófito (Oliveira et al, 2009), sendo que esta última característica se associa à densidade da madeira e altura (Vieira et al, 2008).…”
Section: Constituem Uma Parte Importante Na Comunidade Vegetal De áRe...unclassified
“…As briófitas são frequentemente encontradas em sítios úmidos e sombreados (Gradstein et al, 1996), e algumas características dos forófitos como diâmetro (Bates, 1992), córtex rugoso e pH ácido (Acebey et al, 2003) influenciam em seu estabelecimento (Bataghin et al, 2012).…”
Section: Introdução Geralunclassified